Pengaruh Penggunaan Media Sosial Dan Inovasi Produk Terhadap Perkembangan Usaha (Studi Kasus Pada UMKM di Kecamatan Kanigaran Kota Probolinggo) - Zailuis, Monica I’mal; Nurhidayah, Nurhidayah; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study is to find out and analyze how the Influence of Social Media Use and Product Innovation on Business Development in MSME actors in Kanigaran District, Probolinggo City. The population in the study was MSME actors in Kanigaran District, Probolinggo City and used a sample consisting of 70 respondents. The method used in this study uses multiple linear regression analysis with SPSS test tool version 23. The results of the study were obtained The influence of Social Media and Product Innovation had a positive and significant effect both simultaneously and partially on Business Development. Keywords: Social Media, Product Innovation, Business Development, MSMEs